2009
DOI: 10.1039/b907309b
|View full text |Cite
|
Sign up to set email alerts
|

Detection of prostate specific antigen with nanomechanical resonators

Abstract: In this work, we use arrays of nanomechanical resonators to detect prostate specific antigen (PSA), a protein biomarker associated with prostate cancer. The surfaces of our very thin, trampoline-like devices are functionalized for immunospecific capture of PSA molecules, and the mass of bound material can be detected as a reduction in the resonant frequency. Fetal bovine serum was spiked with known concentrations of PSA, and in conjunction with a nanoparticle-based sandwich assay, concentrations as low as 50 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 21 publications
(25 reference statements)
1
74
0
Order By: Relevance
“…A sample line (5) connected to the sample reservoir (not shown) carries the sample fluid to the injection valve (6) where it is injected into the flow of the inlet buffer. The injection valve is held in place using a manifold mount (4). The fluid can then flow out through the priming line (8) or into the measurement chamber (2) depending on the orientation of the solenoid valve (not shown).…”
Section: Fluidic Chamber Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…A sample line (5) connected to the sample reservoir (not shown) carries the sample fluid to the injection valve (6) where it is injected into the flow of the inlet buffer. The injection valve is held in place using a manifold mount (4). The fluid can then flow out through the priming line (8) or into the measurement chamber (2) depending on the orientation of the solenoid valve (not shown).…”
Section: Fluidic Chamber Assemblymentioning
confidence: 99%
“…Figure 2 Chamber cross section. The cantilever array (6) is clamped in place using a PEEK clamp (4). An Oring (2) and the glass cover (3) allow the creation of a sealed measurement chamber.…”
Section: Fluidic Chamber Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Waggoner et al [19] have used arrays of nanomechanical resonators to detect prostate-specific antigens (PSAs). They have shown that membrane resonators have a relatively uniform frequency response for the mass of bound material located anywhere across its central paddle because of its unique resonant mode shape.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, these characteristics open up microfluidics as a promising device of POCT, and many efforts have been made. [11][12][13] However, most of them were hooked up to an external pumping system, electric power supply 11 and complicated fluidic designs. 12,13 It is demanded to progress further in microfluidics with not only simpler and more compact device integrating the external power sources but also user-friendliness.…”
Section: Introductionmentioning
confidence: 99%